HPV High Risk and Protective Behaviors: The Effects of Religious Affiliation - Wigfall, Lisa (Journal of religion and health, 2012)
The majority of Americans identify themselves as belonging to some religious group. There is a mixed body of literature on whether or not religious affiliation has an influence on engaging in risky behaviors among young adults attending college. This study examined associations between religious affiliation, risky sexual practices, substance use, and family structure among a sample of predominantly white college females attending a southeastern university. Given the high risk of acquiring genital human papillomavirus infection as a result of high risk sexual practices, gaining a better understanding of how religious affiliation can be used to promote healthy sexual behaviors is warranted.